An Analysis of Translation Errors (A case Study of Students at SMAN 2 Wawonii Tenggara) - Yeni Yeni; Tambunan Tambunan; La Ino (Halu Oleo University, 2024)
This study examined the errors made by students in translating Indonesian into English using the surface category taxonomy. The research was conducted at SMAN 2 Wawonii Tenggara, focusing on first-grade students. Specifically, the research included all 20 students from class X.IPA. To gather data, the researcher employed a test consisting of 20 Indonesian sentences. The analysis was carried out using a qualitative descriptive method. The results indicated that the students made a total of 222 errors (55.5%) in translating Indonesian into simple English sentences. These errors were categorized into four types: omission errors (112 or 50.45% of the total), malformation errors (75 or 33.79%), addition errors (32 or 14.41%), and misordering errors (3 or 1.35%). Omission errors were the most frequent. Given that the students made 222 errors (55.5% of possible errors), the correct responses numbered 178 (44.5%). According to Rod Ellis, this number classifies the students' ability as poor.